Ion Selective Carbon Paste Electrode for Determination of Flavoxate Muscle Relaxant Drug in Pharmaceutical Formulation: Potentiometric Determination of Flavoxate - Nahla S. Ismail, (Iranian Journal of Pharmaceutical Sciences, 2016)
The utility of carbon paste electrode for the determination of flavoxate HCl modified with flavoxate-tetraphenylborate (FLX-TPB) and flavoxate-phosphotungestic acid (FLX-PTA) ion-pairs in batch mode is demonstrated. The electrodes revealed a Nernstian response over a wide concentration ranges 1.39×10-5-1x10-2 mol L-1 and1×10-5-1x10-2 mol L-1 using FLX-TPB and FLX-PTA, respectively. The detection limits of these sensors are 1.39×10-5 mol L-1, and 1x10-6 mol L-1 using FLX-TPB and FLX-PTA, respectively. The best performance was obtained with carbon paste composition of 5% flavoxate-tetraphenylborate or flavoxate-phosphotungestate, 47.5% graphite and 47.5% o- nitro phenyl octyl ether (o-NPOE). The sensors exhibit a very fast response time (5-7 s) and good selectivity in presence of inorganic cations, sugars and aminoacids. The proposed sensors show great improvement in comparison with other previously reported sensors. The sensors were successfully applied to monitoring of flavoxate in pure solution and pharmaceutical formulation (Genurin tablet) with recovery ranges from 97.2 – 101.0% and 98.1-101.6% using FLX-TPB and FLX-PTA, respectively.